Ionospheric density oscillations associated with recurrent prompt penetration electric fields during the space weather event of 4 November 2021 over the East-Asian Sector - Singh, Ram; Lee, Y. S.; Song, S. M.; Kim, Y. H.; Yun, J. Y.; Sripathi, S.; Rajesh, B. (My University, 2022)
We found the signatures of the multiple prompt penetration electric fields and the disturbance dynamo electric field having impacts on the East Asian sector ionosphere along the meridional chain thoroughly from the equator, low-mid to high latitudes during the space weather event of 3–5 November 2021. The observation is made on global positioning system-total electron content (GPS-TEC), digisonde, and magnetometer stations. In the main phase of the storm, intense modulations of vertical total electron content (VTEC) and critical frequency (foF2) are observed as coherently fluctuating with interplanetary electric field (IEF) and IMF Bz reorientations. It is diagnosed that the oscillations in the disturbance polar current 2 (DP2) current system directly penetrate meridianally from high to equatorial latitudes, leading to the significant changes in ionospheric electrodynamics that governs the density fluctuations. The wavelet spectra of VTEC, foF2, h’F (virtual height), H-components and IEF give a result of common and dominant periodicity occurring at ∼1 hr. This result suggests that the wavelike oscillations of VTEC and foF2 and H component are associated with prompt penetration electric fields. Plain Language Summary Geomagnetic storm time electrodynamics of the ionosphere is severely affected by magnetospheric convection electric field induced by solar wind-induced magnetospheric dynamo, and ionospheric disturbance dynamo (DD) generated by global thermospheric wind circulation and joule heating at high latitude. The Magnetospheric convection electric field can penetrate instantly into the equatorial ionosphere known as prompt penetration (PP) electric field, while, the thermospheric wind and its associated disturbances can reach the equator with a time delay. During the main phase of the storm, observations showed intense modulations in vertical total electron content (VTEC), critical frequency from equator to high latitudes associated with PP electric fields. In recovery phase, disturbances in VTEC, foF2, and virtual height (h’F) are caused by either DD electric field or traveling ionospheric disturbances. Further analysis in this study suggests the evidence of causal relationship among the interplanetary electric field, disturbance polar current 2 current system, and ionospheric density oscillations. Wavelets analysis shows a common and dominant periodicity of ∼1 hr in interplanetary and ionospheric parameters.
Keywords: Prompt penetration electric fields; PPEF; Ionospheric density oscillations; East-Asian Sector; Space Weather Event